Career commitment and career entrenchment among Primary Health Care workers - Luciano Garcia Lourenção; Jacqueline Flores de Oliveira; Francisco Rosemiro Guimarães Ximenes Neto; Carlos Leonardo Figueiredo Cunha; Sandra Verónica Valenzuela-Suazo; Márcio Andrade Borges; Cláudia Eli Gazetta (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Assess levels of career commitment and career entrenchment among Primary Health Care workers. Methods: This Cross-sectional study addressed 393 workers using the Brazilian versions of the Career Commitment Measure (CCM) and Career Entrenchment Measure (CEM). Results: Levels of Career commitment [75.5-77.5] were higher (p<0.001) than Career Entrenchment [66.7-69.2]. Identity levels [82.7-85.5] were higher (p<0.001) than Investment levels [60.4-65.0]. Career resilience levels [75.1-79.2] were higher (p<0.001) than Emotional costs [69.0-72.1]. Planning levels [64.2-67.1] were lower (p<0.001) than levels of limitedness of career alternatives [68.1-71.0]. Conclusion: The highest scores were obtained in Career commitment, showing the workers' identification and positive relationship with their careers, that is, these workers remain in Primary Health Care services because they identify themselves with their professions.